Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s40097-014-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Microwave synthesis of copper oxide nanoparticles using tea leaf and coffee powder extracts and its antibacterial activity

Abstract: Oxides of copper have been investigated for decades due to their unique semiconductor and optical properties. The review of literature revealed that very few reports are available on the synthesis of copper oxide nanoparticles using microorganisms and plant extracts. In this paper, we have reported the synthesis of copper oxide nanoparticles (CuO) using tea leaf and coffee powder extracts under microwave irradiations. The synthesis was carried out by irradiating metal salt and the extracts of tea and coffee in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(69 citation statements)
references
References 26 publications
5
59
1
1
Order By: Relevance
“…Ascorbic acid may act as a reducing and stabilizing agent for the formation of CuO nanocomposites. Similar to our report, Sutradhar et al [15] visualized color change of copper oxide nanoparticles from light orange to brownish-black color when adding coffee powder extract to copper salt.…”
Section: Synthesis Of Chi-cuo Nanocompositessupporting
confidence: 91%
“…Ascorbic acid may act as a reducing and stabilizing agent for the formation of CuO nanocomposites. Similar to our report, Sutradhar et al [15] visualized color change of copper oxide nanoparticles from light orange to brownish-black color when adding coffee powder extract to copper salt.…”
Section: Synthesis Of Chi-cuo Nanocompositessupporting
confidence: 91%
“…The UV-visible spectra did not change even after a prolonged storage. The spectra clearly agree with the result enlightens that the synthesized nanoparticles were found to be symmetrical, with spherical in nature [16][17]24 ]. …”
Section: Uv-vis Studysupporting
confidence: 88%
“…are given much attention. In literature, biofabrication of CuO-NPs using magnolia leaf/plant extract [14], yeast, and fungi [15], algae [16], tea leaf and coffee powder [17] has been already reported.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectra of CuA AA , CuC AA , and CuS AA nanoparticles showed peaks at 250-270 nm, whereas, in the respective CuNPs/agar BNC films the absorption peaks were broader and shifted to 240 nm. Sutradhar et al (2014) reported the absorption peaks of CuO nanoparticles at 271 and 269 nm synthesized by tea and coffee extract, respectively.…”
Section: Optical Properties and Surface Structure Analysismentioning
confidence: 99%